Morphological Changes in the Liver of Rats (Rattus norvegicus) treated with different Doses of Doxorubicin - Al-Saleem, Ilham A.; Jumaa, Hamad J.; Al-Ani, Imad Matloub Dally; Ismael, Hanaa Kh. (Microscopy Society (Singapore), 2017)
The aim of the present study was to investigate the hepatoxicity of doxorubicin in albino rats (Rattus norvegicus) using different doses and variable durations. Fifty five male rats were divided into two groups, the first group include 35 rats treated intraperitoneal twice a week(every 84 hr) for 3 weeks, 30 rats were treated with doxorubicin at dose (1, 2, 3, 4, 5, 6) mg/kg, and 5 rats served as control and treated with normal saline. The second group includes 20 rats treated twice a week (every 84hr) for 6 weeks, 15 rats were treated with doxorubicin at the dose (1, 2, 3) mg/kg, while 5 rats served as control. The animals were sacrifced at 48 hours postoperative last treatment day; specimens of liver were fixed in 10% neutral buffered formalin for 72 hours, and processed for light microscopy. The liver parenchyma of DOX treated rats for 3 weeks revealed degenerative changes in most of the hepatic lobules; there was vacuolar degeneration of hepatocytes, haemorrhage in the portal area, dilation of the central vein associated with mononuclear infltration, haemorrhage and centrilobular coagulative necrosis of the of the hepatocytes. Administration of DOX for 6 weeks induced severe degenerative changes showing distorted liver architecture in most of the hepatic lobules. These pathological changes of the liver tissue were more severe with the higher doses and the duration of the treatment.